Neosporosis: a neglected abortifacient disease in Egypt, seroprevalence and farmers’ knowledge, attitudes and practices - GABER, A; HEGAZY, YM; OREIBY, AF; ABDEL WAHAB, T; AL-GAABARY, MH (Journal of the Hellenic Veterinary Medical Society, 2021)
Neosporosis has emerged as a serious disease of cattle and dogs worldwide, causing abortions, neonatal mortalities and massive economic losses in dairy herds. The current study aimed to investigate the burden of Neospora (N.) caninum infection among cows that aborted and to assess knowledge, attitudes, and practices (KAPs) of farmers toward neosporosis in Kafrelsheikh governorate, Egypt. A total of 92 cows that aborted and 25 heifers born from cows that aborted and seropositive for N. caninum infection from 15 dairy herds in different districts of Kafrelsheikh governorate were examined serologically against N. caninum infection using ELISA. A structured questionnaire was built and distributed to 41 farmers in the study area. The overall seroprevalence of N. caninum infection among the examined cows that aborted was 38.04% (35/92). On the other hand, the prevalence of N. caninum infection among the 25 examined heifers born from seropositive cows that aborted was 28% (7/25). The KAPs analysis showed that farmers lack the required information on N. caninum infection and its consequences on dairy farms. The farmers performed risky practices which are responsible for disease entrance and spread on the farm; buy and keeping animals after abortion as well as their heifers. In addition, risk management practices were widespread in dairy farms such as: free movement of dogs, especially stray ones, in 100% of the farms, dogs were able to access and defecate in cattle feed and drinking water sources and had the chance to eat placentas and abortion materials. The current study points out neosporosis as a neglected cause of abortion among cattle in Kafrelsheikh governorate, as well as there is a lack of knowledge and risky practices by the local farmers. These findings may be extrapolated to nearby areas and countries of the same cattle husbandry practices, and veterinary services in such countries should consider neosporosis in their surveillance and control programs.